Suicide risk screening in the school environment: Family factors and profiles. (February 2023) - Weissinger, Guy; Shelby Rivers, Alannah; Atte, Tita; Diamond, Guy
Highlights: Four profiles of youth family environments were identified. The family profile associated with the most conflict and home problems was significantly associated with current suicide risk. Even controlling for school factors and mental health, family profile was associated with youth suicide risk. A minimal disclosure group was identified who would require further and careful assessment. Abstract: Youth suicide is a major issue that schools have begun to address through a variety of approaches. Suicide risk assessment supports identification of students at risk and referral to services. Unfortunately, few suicide risk assessments incorporate family factors which can be useful for understanding level of risk and response options. Using data from 12, 760 students screened in the Pennsylvania Student Assistance Program, this study identified family profiles of students and identified relationship between these profiles and suicide risk. Latent class analysis identified four family profiles (high, moderate, low risk, and minimal disclosure) which were related to suicide risk, school concerns (academic performance, bullying) and mental health concerns (depression severity, anxiety). Hierarchical regression modeling found that inclusion of the family risk profiles in assessment models showed significant improvement in identification of suicide risk. Overall, inclusion of family risk profiles improves suicide risk assessment and allows for more holistic and targeted responses by schools.